Palma and Zorrilla - Holguín Callo, Oswaldo (2020)
This article describes the relationship of Peruvian romantic authors with Spanish literature, with special emphasis on Jose Zorrilla’s connections with the group of “bohemians” that Ricardo Palma portrays in his book La bohemia de mi tiempo, and mainly Zorrilla’s relationship with the author of Tradiciones. The two writers had a fluid epistolary exchange and they met in Madrid when Palma was there as a Peruvian envoy for the celebrations of Columbus’ fourth centenary. In addition to the social connections, Zorrilla’s literary influences on the writing of the “bohemians” and Palma himself are highlighted.